2011
DOI: 10.1002/pola.24659
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of biobased epoxy resins. part 1. Glycidylation of flavonoids by epichlorohydrin

Abstract: Biobased epoxy resins were synthesized from a catechin molecule, one of the repetitive units in natural flavonoid biopolymers also named condensed tannins. The reactivity of catechin toward epichlorohydrin to form glycidyl ether derivatives was studied using two model compounds, resorcinol and 4-methylcatechol, which represent the A and B rings of catechin, respectively. These model molecules clearly showed differences in reactivity upon glycidylation, explaining the results found with catechin monomer. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
149
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(157 citation statements)
references
References 28 publications
3
149
0
Order By: Relevance
“…We have shown that the skin sensitization potency of the epoxy resin monomer DGEBF is due to its terminal epoxide groups. Based on our findings, newly reported epoxy resin monomers 50,51 would be expected to cause skin sensitization and allergic contact dermatitis as they contain terminal epoxide groups. Our results also imply that there is a need for further research to try to decrease the reactivity of the epoxide groups to a level where the contact sensitization is reduced but the polymerization capacity is still intact.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that the skin sensitization potency of the epoxy resin monomer DGEBF is due to its terminal epoxide groups. Based on our findings, newly reported epoxy resin monomers 50,51 would be expected to cause skin sensitization and allergic contact dermatitis as they contain terminal epoxide groups. Our results also imply that there is a need for further research to try to decrease the reactivity of the epoxide groups to a level where the contact sensitization is reduced but the polymerization capacity is still intact.…”
Section: Resultsmentioning
confidence: 99%
“…The former are esters of gallic acid (gallo-and ellagitannins) while the latter are polymers of polyhydroxyflavan-3-ol monomers, also known as catechins. 148 In our previous work, 149 catechin was reacted with epichlorohydrin in alkaline medium to lead to the expected tetraglycidyl ether of catechin along with a benzodioxane derivative. The formation of this cyclic by-product is related to the ortho positions of the two phenolic hydroxyl groups carried by the B-ring of catechin.…”
Section: Iii1 Epichlorohydrin Synthesis Of Phenolic Epoxy Prepolymersmentioning
confidence: 99%
“…Biobased epoxy resins were synthesized from a catechin molecule, one of the repetitive units in natural flavonoid biopolymers in condensed tannins and from both flavonoid and hydrolysable tannins themselves (Nouailhas et al 2011). Their reactivity towards epichlorohydrin to form glycidyl ether derivatives was studied.…”
Section: Epoxy Resinsmentioning
confidence: 99%
“…While epoxy resins are rarely used for wood due to their high price, nonetheless it is of interest that epoxy resins derived from wood and bark-derived natural materials have been developed (Nouailhas et al 2011;Aouf et al 2013) in competition with biobased epoxy resins obtained from vegetable oils (Stemmelen et al 2011). Biobased epoxy resins were synthesized from a catechin molecule, one of the repetitive units in natural flavonoid biopolymers in condensed tannins and from both flavonoid and hydrolysable tannins themselves (Nouailhas et al 2011).…”
Section: Epoxy Resinsmentioning
confidence: 99%